The impact of war on the development and progression of arterial hypertension and cardiovascular disease: protocol of a prospective study among Ukrainian female refugees - Shalimova, A.; Stoenoiu, M. S.; Cubała, W. J.; Burnier, M.; Persu, A.; Narkiewicz, K. (Frontiers in Cardiovascular Medicine, 2024)
Background: Growing evidence supports the impact of psychological factors such as traumatic experiences and Post Traumatic Stress Disorder (PTSD) on the incidence of arterial hypertension (HTN) and cardiovascular diseases (CVD). The war in Ukraine is exposing million inhabitants to traumatic experiences and severe stress. Part of Ukrainians (mostly women and children) left the country to escape war. We report the protocol of a prospective study aiming at the assessment of the impact of war-induced stress on HTN and CVD in women Ukrainian refugees moved to Poland.The study will be conducted in 3 stages. Stage 1 will assess the prevalence of HTN and PTSD among Ukrainian refugees and will estimate the impact of warrelated trauma exposure on these parameters. Data on office blood pressure (BP) will be compared to data already collected in STEPS data 2019 and May Measurement Month 2021 in Ukraine, matched for age and sex. Stage 2 will involve subjects diagnosed with HTN and/or PTSD referred for management and follow-up of these conditions. Psychologic targeted therapies will be offered to subjects with confirmed PTSD, with a periodical reassessment of the severity of PTSD-associated symptoms and of its impact on HTN and cardiovascular health.Clinical history and characteristics will be compared among three groups: subjects with HTN and PTSD, with HTN without PTSD, with PTSD but without HTN. Stage 3 will involve a subgroup among those screened in Stage 1, with the objective of investigating the biological mechanisms underlying the relation between HTN and trauma exposure, identifying early signs of subclinical target organ damage in subjects with HTN with/without PTSD.Discussion: This study will test the hypothesis that trauma exposure and psychological stress contribute to BP elevation and progression of CVD in this population. It will provide new evidence on the effect of an integrated management, including psychological therapy, on BP and cardiovascular risk. Such approach may be further tested and extrapolated to other populations exposed to war and chronic violence, migrants and refugees around the world.